Styk jurysdykcji sądów powszechnych i administracyjnych w kontekście reprezentacji nieobecnego w postępowaniu administracyjnym i sądowo-administracyjnym - Politowicz, Konrad, Andrzej (Kwartalnik Prawa Publicznego, 2013)
Civil courts and administrative courts functioning in Poland separately. Both have its own range of competences and jurisdiction, including general controlling of administrative proceedings of public institutions by administrative courts. But there are spaces where those activity of mentioned types of courts crosses, what can bring even collision between two – equal from constitutional point of view – jurisdictional organs. Such situation appears e.g. when one of subjects of proceedings – in administrative procedure or process of administration court – is absent and his/her place of residence is unknown. Regulations of code of administrative procedure and so bill of processing of administrative courts obligate organ that leading proceeding to provide competent representative for such person, that is called a curator. Traditionally – since many decades, despite of changes of regime of state – those regulations finding establishment of curator as a competence of civil courts. It is very important competence when lack of mentioned representative can cause even procedural invalidity of every pronounced in that conditions decision. If petition of administrative organs or courts will be not accepted by civil court, their activity may sticks. Looking for remedy for this hardly acceptable situation, is necessary to take a comparative look through jurisdiction of Supreme Court according to article 143 of civil procedure, where – in opinion of Supreme Court – were established special kind of curator: processing curator, who’s representing absent person only in particular proceeding and realizing instead of absent person only his/her straightly procedural powers. That curator is also a special kind of procedural tool using by civil courts, that lets them to keep on proceeding, even while specific situation described above happened. If so, basing on that experience of civil courts, it is quite logical to adopt such institution also in procedural regulations that using administrative courts, and let them independently decide about substitutive representation of absent persons in processing of administrative courts and administration organs (for whom are administrative courts a controlling instance). However as very important for rights of absent person, ability of making such decisions should stay by judicial organs.